OPTIMALISASI STRATEGI THINK TALKWRITE (TTW) UNTUK MENINGKATKAN KEMAMPUAN MENULIS KARANGANTEKS DESKRIPTIF SISWA DI SDN 1 MANIKYANG - I Nyoman Sudiana; I Gusti Agung Ayu Lily Purnami; Ni Luh Nyoman Wina Wahini; Yuni Nuryanti; Putri Hidayah; Gusti Ngurah Bagus Tirtayadna (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the effectiveness of the Think Talk Write (TTW) learning model in improving the descriptive text writing skills of fourth-grade students at SDN 1 Manikyang. The TTW model is implemented as a learning strategy that encourages students to think critically, engage in discussions, and express their ideas in a more structured written form. The research method used is quantitative with an experimental approach, employing a pre-test and post-test design, where data is collected through an assessment of students' writing performance before and after the implementation of the TTW model. The results of the study indicate a significant improvement in students' writing abilities after the application of the TTW model. The average student score increased from 67.94 in the pre-test to 75.00 in the post-test. Before the implementation of the TTW model, the majority of students were in the fair category (58.82%) and poor category (35.29%). However, after the intervention, most students fell into the good category (58.8%) and very good category (20.6%). Furthermore, no students remained in the poor or very poor categories after the implementation.